2020
DOI: 10.1002/anie.202008116
|View full text |Cite
|
Sign up to set email alerts
|

A Surface‐Oxide‐Rich Activation Layer (SOAL) on Ni2Mo3N for a Rapid and Durable Oxygen Evolution Reaction

Abstract: The oxygen evolution reaction (OER) is key to renewable energy technologies such as water electrolysis and metal–air batteries. However, the multiple steps associated with proton‐coupled electron transfer result in sluggish OER kinetics and catalysts are required. Here we demonstrate that a novel nitride, Ni2Mo3N, is a highly active OER catalyst that outperforms the benchmark material RuO2. Ni2Mo3N exhibits a current density of 10 mA cm−2 at a nominal overpotential of 270 mV in 0.1 m KOH with outstanding catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 44 publications
2
53
0
Order By: Relevance
“…According to this, an amorphous cobalt oxide-rich activation surface layer is generated on Co 3 Mo 3 N during OER process, which offers the active sites for OER. 33,[45][46][47] Specifically, the Mo atoms shift toward the inner bulk forming short bonding with N atoms to compensate the influence of dangling bonds in surface. The surface Co atoms get more freedom to be oxidized, which are also expected to offer flexible valence during OER runs, and hence is likely the key source of catalytic activity (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this, an amorphous cobalt oxide-rich activation surface layer is generated on Co 3 Mo 3 N during OER process, which offers the active sites for OER. 33,[45][46][47] Specifically, the Mo atoms shift toward the inner bulk forming short bonding with N atoms to compensate the influence of dangling bonds in surface. The surface Co atoms get more freedom to be oxidized, which are also expected to offer flexible valence during OER runs, and hence is likely the key source of catalytic activity (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The cobalt oxide-rich surface can offer favorable ener-getics for the deprotonation of OH. 47 Meanwhile, the surface Mo atoms can transfer charges and facilitate the reaction continuity as an electron pump. 47 These, in fact, are expected to offer the appropriate energetics and electronic structures for advanced catalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Theoxygen evolution reaction (OER) involves afour-step of proton coupling electron transfer process with sluggish kinetics. [7] High applied potential is needed to drive the water splitting reaction and most of the energy for hydrogen production from water splitting is consumed in the anodic part. [8] Thelow activity of OER reaction in neutral conditions, the electrochemical instability in acidic conditions and the use of precious metal component hinder the green and efficient hydrogen production.…”
mentioning
confidence: 99%
“…Yang and coworkers studied the OER activity of Ni 2 Mo 3 N hetero-metal nitride [207]. They reported that an amorphous surface oxygen-rich activation layer (SOAL) was generated on Ni 2 Mo 3 N nanoparticle surface by applying high oxidative potential in alkaline conditions.…”
Section: Heterogeneous Mo-containing O 2 -Evolution Electrocatalystsmentioning
confidence: 99%